1975
DOI: 10.1128/iai.11.6.1174-1181.1975
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Adoptive Immunity to Tuberculosis in Mice

Abstract: A system is described for studying adoptive immunity to tuberculosis in syngeneic mice. Donor mice were immunized with 104 BCG intravenously, and lymphoid cells were harvested 28 days later. Adoptive immunity was measured in recipient mice in terms of the inhibition of growth of BCG in the liver and spleen following intravenous injection. Adoptive immunity was expressed optimally when recipients were sublethally irradiated (500 R), challenged with 104 to 105 viable organisms, and given sensitized lymphoid cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 19 publications
5
54
0
Order By: Relevance
“…T lymphocytes play an important role in cellular immunity to BCG (32) and Listeria (12), and have been implicated in the activation of m~b by C. parvum (33). Evidence that Ag-stimulated T lymphocytes influence the surface and endocytic properties of mq~, as well as their secretory activity, was obtained by adoptive transfer experiments in vivo and in vitro and by depletion of Thy-1-positive cells with specific Ab and complement.…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocytes play an important role in cellular immunity to BCG (32) and Listeria (12), and have been implicated in the activation of m~b by C. parvum (33). Evidence that Ag-stimulated T lymphocytes influence the surface and endocytic properties of mq~, as well as their secretory activity, was obtained by adoptive transfer experiments in vivo and in vitro and by depletion of Thy-1-positive cells with specific Ab and complement.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings Mackaness [34] made the visionary suggestion 'that acquired resistance to intracellular pathogens depends upon the activation of host macrophages through a product resulting from specific interaction between sensitized lymphoid cells and the organism or its antigenic product.' The subsequent demonstration of T cells as the responsible lymphocyte subset was also contributed by the Trudeau group [35,36]. North [35] demonstrated that thymectomized mice were highly sensitive to TB and Lefford [36] demonstrated that T cells from immune mice protected irradiated recipient mice from TB infection upon adoptive transfer.…”
Section: Immunity To Tuberculosismentioning
confidence: 98%
“…The subsequent demonstration of T cells as the responsible lymphocyte subset was also contributed by the Trudeau group [35,36]. North [35] demonstrated that thymectomized mice were highly sensitive to TB and Lefford [36] demonstrated that T cells from immune mice protected irradiated recipient mice from TB infection upon adoptive transfer.…”
Section: Immunity To Tuberculosismentioning
confidence: 98%
“…This last reaction generates a tissue-damaging delayed hypersensitivity, which is the cytotoxic immune process that results in the killing of non-activated macrophages that have permitted the multiplication of tubercle bacilli within them (Dannenberg, 1994). Both responses are an expression of the lymphocyte-mediated immune response, which has been studied in classical experiments performed with mice, in which the participation of speci®cally sensitized T lymphocytes and mononuclear phagocytes has been described (Lefford, 1975;Orme, 1988). However, there have been no reports on the differences that occur in the circulating T-cell and B-cell subpopulations in caprine tuberculosis and only a few contributions concerning cattle (Pollock et al, 1996).…”
Section: Introductionmentioning
confidence: 99%